Estimation of the centre of mass kinematics in alpine ski racing using inertial and magnetic sensors - Fasel, B.; Gilgien, M.; Spörri, J.; Aminian, K. (ISBS Proceedings Archive (Michigan), 2017)
For performance analysis in alpine ski racing, an accurate and precise estimation of the centre of mass (CoM) kinematics is indispensable. Currently available systems satisfying this need are video-based stereo-photogrammetry or differential global navigation satellite systems (GNSS). However, they are impractical to use in regular training settings. Inertial sensors could be used instead but suffer from significant drifts in speed and position estimation due to the integration of acceleration and angular velocity data. The aim of the present study was to propose and validate an inertial and magnetometer sensor-based algorithm to estimate CoM kinematics in alpine ski racing. Relative CoM position and speed between-run comparisons were found to be highly accurate and precise with mean absolute deviations <0.15 m and <0.28 m/s.